Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood – Interim Analysis of the IMMO-LDRT01 Trial - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta M.; Muñoz, Luis E.; Gryc, Thomas; Denzler, Manuel; Ott, Oliver J.; Fietkau, Rainer; Gaipl, Udo S.; Frey, Benjamin (Frontiers in Immunology, 2021)
The treatment of chronic inflammatory and degenerative diseases by low dose radiation therapy (LDRT) is promising especially for patients who were refractory for classical therapies. LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has been applied since the late 19th century, the immunological mechanisms remain elusive. Within the prospective IMMO-LDRT01 trial (NCT02653079) the effects of LDRT on the peripheral blood immune status, as well as on pain and life quality of patients have been analyzed. Blood is taken before and after every serial irradiation with a single dose per fraction of 0.5Gy, as well as during follow-up appointments in order to determine a detailed longitudinal immune status by multicolor flow cytometry. Here, we report the results of an interim analysis of 125 patients, representing half the number of patients to be recruited. LDRT significantly improved patients’ pain levels and induced distinct systemic immune modulations. While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells. Furthermore, activated immune cells were decreased following LDRT. Especially cells of the monocytic lineage correlated to LDRT-induced improvements of clinical symptoms, qualifying these immune cells as predictive biomarkers for the therapeutic success. We conclude that LDRT improves pain of the patients by inducing systemic immune modulations and that immune biomarkers could be defined for prediction by improved patient stratification in the future.